2017
DOI: 10.1016/j.renene.2016.10.040
|View full text |Cite
|
Sign up to set email alerts
|

Wind power characteristics of seven data collection sites in Jubail, Saudi Arabia using Weibull parameters

Abstract: The wind characteristics of seven locations in Jubail, Saudi Arabia were analysed by using five years of wind data of six sites and three years data of one site at 10 m above ground level (AGL). The highest annual mean wind speed of 4.52 m/s was observed at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
72
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(72 citation statements)
references
References 16 publications
0
72
0
Order By: Relevance
“…Based on Baseer et al [27], the highest mean wind speeds at the Jubail industrial site of 5.35 m/s, and the possibility of wind speeds reaching above 3.5 m/s, was 75%. Another study was conducted by the same team [28] to analyse seven sites at Jubail using different tools. The results showed that the highest annual mean wind speed of 4.52 m/s was observed at Jubail [28].…”
Section: Wind Energymentioning
confidence: 99%
“…Based on Baseer et al [27], the highest mean wind speeds at the Jubail industrial site of 5.35 m/s, and the possibility of wind speeds reaching above 3.5 m/s, was 75%. Another study was conducted by the same team [28] to analyse seven sites at Jubail using different tools. The results showed that the highest annual mean wind speed of 4.52 m/s was observed at Jubail [28].…”
Section: Wind Energymentioning
confidence: 99%
“…The value of wind speed shear exponent follows the setting of Kim and Hur (2017). A Weibull distribution has won its reputation in analyzing wind speed data (Bagiorgas et al, 2012(Bagiorgas et al, , 2016Baseer et al, 2017;Bassyouni et al, 2015;Rehman et al, 2012). The twoparameter Weibull distribution consists of scale and shape parameters, and the distribution of wind speed can be estimated by Weibull distribution.…”
Section: Wind Power Assessmentmentioning
confidence: 99%
“…We firstly performed a distributional analysis to identify the distribution that better describes our wind speed data. The distributions that are generally employed to fit wind speed data are Weibull [26], Gamma [27], and Generalized Extreme Values (GEV) [28].…”
Section: Data and Exploratory Analysismentioning
confidence: 99%